Pilot Randomized Controlled Trial to Reduce Readmission for Heart Failure Using Novel Tablet and Nurse Practitioner Education - Breathett, Khadijah (Am J Med, 2018)
BACKGROUND: Heart failure education programs are not standardized. The best form of education is unclear. We evaluated whether addition of a novel tablet application to nurse practitioner (NP) education was superior to NP education alone in reducing 30-day readmission after heart failure hospitalization. METHODS: From 2/2015–3/2016, patients admitted to a quaternary academic center with primary diagnosis of heart failure were randomized to (1) treatment- NP education plus tablet application (interactive conditional logic program that flags patient questions to medical staff) or (2) control- NP education. The primary outcome was reduction in 30-day readmission rate. Secondary outcomes included satisfaction and education assessed via survey. RESULTS: Randomization included 60 patients to treatment and 66 to control. A total of 13 patients withdrew prior to intervention (treatment n=4, control n=1) or were lost to follow-up (treatment n=3, control n=5). The 30-day readmission rate trended lower for treatment compared to control, but results were not statistically significant [13.2% (7/53), 26.7% (16/60), respectively, p=0.08]. Similarly, satisfaction trended higher with treatment than control (p=0.08). Treatment patients rated explanations from their physicians higher than control (Always: 83.7%, 55.8%, respectively, p=0.01). CONCLUSIONS: NP education plus tablet use was not associated with significantly lower 30-day readmission rates in comparison to NP alone, but a positive trend was seen. Patient satisfaction trended higher and heart failure explanations were better with NP education plus tablet. A larger study is needed to determine if NP education plus tablet reduces readmission rates following heart failure admission.